Lawyer of the administration of justice (Judicial Counsellor) and eviction trials for non-payment: a very relevant legal operator (Acta Judicial Journal, 2019)
We analyze the transcendental intervention of the Judicial Counsellor in the Eviction Trials for non-payment, where he not only directs the processing of the procedure but, in certain cases resolves, creating an executive title that facilitates the eviction of the property and the claim of the rent due. The legislator in 2011 opted to attribute these functions to the Judicial Counsellor, with all the guarantees referring to the respect of the jurisdictional power of Judges and Magistrates enshrined in art. 117 CE (Spanish Constitution), since there is an appeal for review against all the decisions of the judicial public notary and, therefore, there is no doubt about the constitutionality of the attribution. The procedure is regulated in a manner very similar to the payment procedure of arts. 812 et seq. of LEC (Spanish civil procedure Law), and it is for this reason that it is said that it participates in the "payment procedures technique". In addition, some authors consider that the payment procedure could have features that coincide with the Voluntary Jurisdiction. We analyze the relevance of the system of notifications and requirements and the indispensable guarantee work that the Judicial Counsellor must have in order not to cause defenselessness to the defendant, always taking into account the agility of the procedure. And finally, according to the latest legislative reforms, the Judicial Counsellor also becomes a key legal operator to guarantee that Social Services can act in vulnerability situations.
Keywords: Eviction due to non-payment, Judicial Counsellor, Payment Procedures, Voluntary Jurisdiction, Verbal Trial, Edictal Notification, Decrees.